2015
DOI: 10.15690/vramn519
|View full text |Cite
|
Sign up to set email alerts
|

The Predictability of Motor and Cognitive Impairment According to Brain Asymmetry of Cognitive Evoked Potentials P300 and Features of Symptom Complex in Patients with Parkinson’s Disease

Abstract: Проблема прогнозирования развития нейродегенера-тивных заболеваний, в частности болезни Паркинсона (БП), по электроэнцефалографическим критериям оста-ется актуальной. С помощью вейвлет-преобразования частотно-временной структуры электроэнцефалограммы (ЭЭГ) уже на ранних стадиях развития БП у пациентов регистрируется дезорганизация ведущего ритма, особен-но в центральных отведениях ЭЭГ, формирование актив-ности 4-6 Гц, синхронизированной с электромиогра-фической активностью и тремором конечностей [1]. По повыше… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The priority of temporal brain areas in the lengthening of both recognition and motor components of the ERPs may be related not only to vascular abnormalities, but also to the accession of neurodegenerative disorders. In our previous studies, it was shown that the severity of signs of such a neurodegenerative disease as Parkinson's disease correlates with a decrease in ERP P300 parameters in temporal and especially anterior temporal regions [21]. It has also been noted that in Alzheimer's disease, the stronger cerebral ERP P300 generators often shift from the frontal lobes to the temporal regions.…”
Section: Discussionmentioning
confidence: 94%
“…The priority of temporal brain areas in the lengthening of both recognition and motor components of the ERPs may be related not only to vascular abnormalities, but also to the accession of neurodegenerative disorders. In our previous studies, it was shown that the severity of signs of such a neurodegenerative disease as Parkinson's disease correlates with a decrease in ERP P300 parameters in temporal and especially anterior temporal regions [21]. It has also been noted that in Alzheimer's disease, the stronger cerebral ERP P300 generators often shift from the frontal lobes to the temporal regions.…”
Section: Discussionmentioning
confidence: 94%